Decompensated Heart Failure with Mid-Range Ejection Fraction: Epidemiology and In-Hospital Mortality Risk Factors - Cavalcanti,Gabriela Paiva (2020)
Abstract Background: Recently, a new HF entity, with LVEF between 40-49%, was presented to comprehend and seek better therapy for HF with preserved LVEF (HFpEF) and borderline, in the means that HF with reduced LVEF (HFrEF) already has well-defined therapy in the literature. Objective: To compare the clinical-therapeutic profile of patients with HF with mid-range LVEF (HFmrEF) with HFpEF and HFrEF and to verify predictors of hospital mortality. Method: Historical cohort of patients admitted with decompensated HF at a supplementary hospital in Recife/PE between April/2007 - August/2017, stratified by LVEF (< 40%/40 - 49/≥ 50%), based on the guideline of the European Society of Cardiology (ESC) 2016. The groups were compared and Logistic Regression was used to identify predictors of independent risk for in-hospital death. Results: A sample of 493 patients, most with HFrEF (43%), HFpEF (30%) and HFmrEF (26%). Average age of 73 (± 14) years, 59% men. Hospital mortality 14%, readmission within 30 days 19%. In therapeutics, it presented statistical significance among the 3 groups, spironolactone, in HFrEF patients. Hospital death and readmission within 30 days did not make difference. In the HFmrEF group, factors independently associated with death were: valve disease (OR: 4.17, CI: 1.01-9.13), altered urea at admission (OR: 6.18, CI: 1.78-11.45) and beta-blocker hospitalization (OR: 0.29, CI: 0.08-0.97). In HFrEF, predictors were: prior renal disease (OR: 2.84, CI: 1.19-6.79), beta-blocker at admission (OR: 0.29, CI: 0.12-0.72) and ACEI/ ARB (OR: 0.21, CI: 0.09-0.49). In HFpEF, only valve disease (OR: 4.61, CI: 1.33-15.96) and kidney disease (OR: 5.18, CI: 1.68-11.98) were relevant. Conclusion: In general, HFmrEF presented intermediate characteristics between HFrEF and HFpEF. Independent predictors of mortality may support risk stratification and management of this group.